Swedish quality registry for caries and periodontal diseases (SKaPa): validation of data on dental caries in 6- and 12-year-old children - Tita Mensah; Sofia Tranæus; Andreas Cederlund; Aron Naimi-Akbar; Gunilla Klingberg (BMC, 2021)
Abstract Background The Swedish Quality Registry for caries and periodontal disease (SKaPa) automatically collects data on caries and periodontitis from patients' electronic dental records. Provided the data entries are reliable and accurate, the registry has potential value as a data source for registry-based research. The aim of this study was to evaluate the reliability and accuracy of the SKaPa registry information on dental caries in 6- and 12-year-old children. Method This diagnostic accuracy study compared dental caries data registered at an examination with dental health status registered in the patient's electronic dental records, and with corresponding data retrieved from the SKaPa registry. Clinical examinations of 170 6- and 12-year-old children were undertaken by one of the researchers in conjunction with the children's regular annual dental examinations where the number of teeth were registered, and dental caries was diagnosed using ICDAS II. Teeth with fillings were defined as filled and were added to the ICDAS II score and subsequently dft/DFT was calculated for each individual. Cohen's Kappa, the intraclass correlation coefficient (ICC), and sensitivity and specificity were calculated to test the agreement of the 'decayed and filled teeth' in deciduous and permanent teeth (dft/DFT) from the three sources. Results Cohen's Kappa of the dft/DFT-values was calculated to 0.79 between the researcher and the patient record, to 0.95 between patient dental record and SKaPa, and to 0.76 between the researcher and SKaPa. Intraclass correlation coefficient (ICC) was calculated to 0.96 between the researcher and the patient journal, to 0.99 between the patient dental record vs. SKaPa, and to 0.95 between the researcher and SKaPa. Conclusion The SKaPa registry information demonstrated satisfactory reliability and accuracy on dental caries in 6- and 12-year-old children and is a reliable source for registry-based research. Trial registration The study was registered in Clinical Trials ( www.ClinicalTrials.gov , NCT03039010)